Aspectos fisiológicos e produtividade de genótipos de mamona de porte baixo influenciados por densidades de plantas - Pivetta, Laerte Gustavo [UNESP] (2014)
The use of short castor hybrid grown under high populations can increase productivity due to higher light interception and vegetative sink reduction. The aim of this study was to evaluate the effect of plant density of castor hybrids on physiological and productive aspects. The experiments were carried at the Experimental Farm Lageado, in Botucatu, SP, in out-of-season, in 2011 and 2012. The experimental design was a randomized block in factorial scheme 3 x 3 with three genotypes and three plant populations. The genotypes used were hybrids 1 and 2 and the IAC 2028 cultivar in 2011 and the hybrid 3 and 4 and IAC 2028 cultivar in 2012. The plant populations used were 20, 40 and 80 thousand plants per hectare. All plots were sown with spacing 0,45 m. The largest growth occurred in 2012 due to higher water availability. Due to this fact, the castor plant branched out more in 2012, with quaternary branches in hybrids, even in the larger population. The larger branching in 2012 increased shading and reduced primary and secondary leave lifespan. Regarding the productive aspects were observed reduction of number of racemes per plant and number of grains per raceme with the increase of plant population. IAC 2028 showed less racemes but had greater grain production per raceme under good water conditions. Yield was higher in larger populations in both years and IAC 2028 was higher than the Hybrid 2 in 2011. In 2012 there was no difference in yield between genotypes. In 2011 Hybrid 2 had the lowest oil content and there was no difference between the populations. In 2012 there was no difference in oil content between the genotypes and the plant population of 80 thousand plants was higher ...